Theoretical study on the protonation of cucurbit[7]uril - Makrlík, Emanuel; Toman, Petr; Vanura, Petr (Acta chimica Slovenica, 2013)
By using quantum mechanical DFT calculations, the most probable structures of the cucurbit[7]urilH3O+ and cucur-bit[7]uril'(H3O+)2 cationic complex species were derived. In these two complexes having a plane symmetry, each of the considered H3O+ cations is bound by relatively strong hydrogen bonds to the corresponding carbonyl oxygens of the parent cucurbit[7]uril macrocycle.
Keywords: přemostěné cyklické sloučeniny; Imidazoles; protony; Models, Molecular; Protons; teoretické modely; molekulární modely; Models, Theoretical; Bridged-Ring Compounds; imidazoly